A novel balanced‐to‐unbalanced branch‐line coupler with large power division ratio. Issue 2 (22nd October 2021) - Zhu, Zihui; Wang, Zhongbao; Han, Peng; Liu, Hongmei; Fang, Shaojun
Abstract: A novel balanced‐to‐unbalanced branch‐line coupler with a large power division ratio (PDR) is proposed in this paper. The proposed coupler consists of six transmission‐line sections, which can be easily synthesized with the prescribed PDR. By changing the electrical lengths of two transmission lines, a large PDR range can be obtained without the use of high‐impedance transmission lines. The closed‐form design equations are provided and discussed. To verify the proposed circuit, a coupler prototype with the PDR of 20 dB and the center frequency of f 0 = 1.0 GHz is designed and fabricated. Simulation and measurement results are in good agreement. When the balanced port A is excited, the measured differential‐mode to single‐ended transmission coefficients at f 0 for the unbalanced ports D and C are | S sdDA | = −0.28 dB and | S sdCA | = −20.02 dB, respectively, which meet the desired PDR. The measured | S ddAA | at f 0 is −33.6 dB with a −10‐dB bandwidth of about 12.7% from 0.933 to 1.059 GHz. The | S scDA | and | S scCA | are less than −29.5 dB with a −18‐dB bandwidth of 22.4% from 0.924 to 1.157 GHz.